2018
DOI: 10.1038/s41594-018-0086-9
|View full text |Cite|
|
Sign up to set email alerts
|

Structure of the core of the type III secretion system export apparatus

Abstract: Export of proteins through type III secretion systems is critical for motility and virulence of many major bacterial pathogens. Three putative integral membrane proteins (FliP, FliQ, FliR) are suggested to form the core of an export gate in the inner membrane, but their structure, assembly and location within the final nanomachine remain unclear. Here, we present the cryoelectron microscopy structure of the Salmonella Typhimurium FliP-FliQ-FliR complex at 4.2 Å. None of the subunits adopt canonical integral me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
298
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 155 publications
(309 citation statements)
references
References 44 publications
(86 reference statements)
10
298
0
1
Order By: Relevance
“…The core export apparatus components SctR, SctS and SctT form a helical assembly with nearly the same helical parameters as the needle filament: about 5.5 subunits per turn and a helical rise of about 4.0 Å per subunit (Kuhlen et al , ). These data suggest that the core export apparatus templates assembly of the helical filament and thus, also the inner rod should possess these helical properties.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The core export apparatus components SctR, SctS and SctT form a helical assembly with nearly the same helical parameters as the needle filament: about 5.5 subunits per turn and a helical rise of about 4.0 Å per subunit (Kuhlen et al , ). These data suggest that the core export apparatus templates assembly of the helical filament and thus, also the inner rod should possess these helical properties.…”
Section: Resultsmentioning
confidence: 99%
“…The inner rod itself is anchored to the core export apparatus components SctR and SctT, that, together with SctS, also form a helical assembly with nearly identical helical parameters as the needle filament ( Fig. 1B,C) (Dietsche et al, 2016;Kuhlen et al, 2018;Johnson et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The high level of sequence conservation within all T3SS implied that this complex would be similarly assembled in virulence T3SS. Native mass spectrometry (nMS) of purified virulence system complexes supported this, revealing a core SctR5T1 complex equivalent to FliP5R1 (Kuhlen, Abrusci et al 2018). However, the number of SctS subunits was highly variable in samples and seemed to reflect lower stability of these complexes c.f.…”
Section: Introductionmentioning
confidence: 90%
“…We have recently demonstrated that a subset of these proteins assembles into a core exportgate complex, and reported the structure of a flagellar FliP5Q4R1 (hereafter termed FliPQR) complex at 4.2 Å structure by cryo-electron microscopy (Kuhlen, Abrusci et al 2018). Strikingly placing the FliPQR structure into lower resolution basal body structures revealed that this complex, built from three putative membrane proteins and purified from membranes when expressed in isolation of the rest of the T3SS, physiologically exists in an 20 extra-membrane location at the core of the basal body (Worrall, Hong et al 2016, Kuhlen, Abrusci et al 2018}. This positioning of the complex, in conjunction with the observation that it exhibits helical symmetry, suggested that it seeds assembly of the axial helical components that culminate in the flagellum or needle.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation